Stochastic analysis with financial applications Hong Kong 2009 - Kohatsu-Higa, Arturo; Privault, Nicolas; Sheu, Shuenn-Jyi 1958- (Basel, Switzerland Birkhäuser Basel, 2011)
Stochastic analysis has a variety of applications to biological systems as well as physical and engineering problems, and its applications to finance and insurance have bloomed exponentially in recent times. The goal of this book is to present a broad overview of the range of applications of stochastic analysis and some of its recent theoretical developments. This includes numerical simulation, error analysis, parameter estimation, as well as control and robustness properties for stochastic equations. The book also covers the areas of backward stochastic differential equations via the (non-linear) G-Brownian motion and the case of jump processes. Concerning the applications to finance, many of the articles deal with the valuation and hedging of credit risk in various forms, and include recent results on markets with transaction costs. Contributors: T.R. Bielecki, N. Bouleau, S. Chakraborty, T.S. Chiang, S.N. Cohen, J.M. Corcuera, S. Crépey, A.B. Cruzeiro, L. Denis, J. Duan, R.J. Elliott, S. Fang, M. Fukasawa, F.Q. Gao, B. Goldys, S. Han, Y. Ishikawa, M. Jeanblanc, H. Jiang, B. Jourdain, A. Kohatsu-Higa, E.T. Kolkovska, H. Lee, L. Li, J.A. López-Mimbela, J. Luo, B. Øksendahl, J. Ren, M. Rutkowski, E. Shamarova, S.J. Sheu, A. Sulem, A. Takeuchi, N. Vaytis, R. Wang, J. Wei, J. Wu, J. Yang, H. Yang, K. Yasuda, X. Zhan
Keywords: Stochastic differential equations -- Congresse; Stochastic analysis -- Congresse